APTWG: The 5th Asia-Pacific Transport Working Group Meeting. (8th February 2016) - Gao, X.; Ghim, Y.-C.; Sun, Y.W.; Gao, Z.; Inagaki, S.; Chen, W.; Zhang, T.; Wang, Z.X.
Abstract: This conference report gives a summary on the contributed papers and discussions presented at the 5th Asia-Pacific Transport Working Group Meeting held at Dalian, China from 9–12 June 2015. The main goal of the working group is to develop a predictive understanding of the basic mechanisms responsible for particle, momentum and energy transport in magnetically confined plasmas. The topics of the meeting in 2015 were organized under five main headings: (1) turbulence suppression and transport barrier formation, (2) effect of magnetic topology on MHD activity and transport, (3) non-diffusive contribution of momentum and particle transport, (4) non-local transport and turbulence spreading and coupling and (5) energetic particles and instability. The Young Researchers' Forum which was held at this meeting is also described in this report.